2017
DOI: 10.1155/2017/6235398
|View full text |Cite
|
Sign up to set email alerts
|

Report on 14 Large Whales That Died due to Ship Strikes off the Coast of Sri Lanka, 2010–2014

Abstract: The greatest threat to cetaceans in Sri Lankan waters was considered to be the direct take of small-and medium-sized cetaceans using harpoons and/or as bycatch until recently. However, ship strikes have probably been occurring for years but have not been recognized for what they were. For the current study, only animals with visible and prominent injuries related to collisions were evaluated. Data gathered between 2010 and 2014 included the species, morphometry, location, and date; tissue samples were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Here, we have documented and described blunt trauma in a dead pilot whale. Fractured vertebrae can occur when whales collide with fast-moving, heavy ships [ 14 ]. In this case, we identified major internal head and neck lesions that were not visible from the outside.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we have documented and described blunt trauma in a dead pilot whale. Fractured vertebrae can occur when whales collide with fast-moving, heavy ships [ 14 ]. In this case, we identified major internal head and neck lesions that were not visible from the outside.…”
Section: Discussionmentioning
confidence: 99%
“…The whales here are naturally at greatest risk at the surface. However, previous studies have shown that whales are more vulnerable to collision when they feed and socialize [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The continental slope region also coincides with one of the busiest shipping routes in the world (Priyadarshana et al 2016). Over 5000 ships pass through these waters every month (Nanayakkara & Herath 2017) (Fig. 1).…”
Section: Study Areamentioning
confidence: 93%
“…The general issue is that an extensive shipping lane crosses an area populated by cetaceans in the southern territorial sea, and oil, chemicals, toxic materials, and other goods are constantly transported by various large vessels (de Vos et al 2016). In the case of an accidental ship-to-whale collision, cetaceans and all marine organisms living in the area can be significantly affected (Randage et al 2014;Priyadarshana et al 2016;Nanayakkara & Herath 2017).…”
Section: Possible Threats: Conservation and Management Implicationsmentioning
confidence: 99%
See 1 more Smart Citation